2004
DOI: 10.1149/1.1688796
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Capacity Fading Mechanism for Fe-Substituted LiCoO[sub 2] Positive Electrode

Abstract: To find the origin of a large initial irreversible capacity and capacity fading with cycling for Fe-substituted LiCoO 2 (LiCo 1Ϫy Fe y O 2 ), the LiCo 0.8 Fe 0.2 O 2 positive electrode was selected for study by ex situ X-ray diffraction, Co and Fe K-edge X-ray absorption, and 57 Fe Mössbauer spectroscopies. A disordering of Fe ions from 3b͑0, 0, 1/2͒ to 6c͑0, 0, 3/8͒ sites was detected for initial charged samples through X-ray Rietveld analysis and Co and Fe K-edge X-ray absorption near-edge structures and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Owing to that Fe 3+ are energetically stable at tetrahedral sites, Fe 3+ could easily migrate to the face-shared sites, which is similar to LiCo x Fe 1−x O 2 . [53] The solid-state diffusion of Na + are thus blocked, inducing degradation of electrode properties. Lee et al [45] found that Jahn-Teller-active Fe 4+ in the desodiate Na 1−x FeO 2 were not stable with more than 20% of Fe 4+ species spontaneously reduced to Fe 3+ states by the electrolyte during open-circuit storage of the charged cell.…”
Section: Single-metal-based Oxides Peculiar To Sibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to that Fe 3+ are energetically stable at tetrahedral sites, Fe 3+ could easily migrate to the face-shared sites, which is similar to LiCo x Fe 1−x O 2 . [53] The solid-state diffusion of Na + are thus blocked, inducing degradation of electrode properties. Lee et al [45] found that Jahn-Teller-active Fe 4+ in the desodiate Na 1−x FeO 2 were not stable with more than 20% of Fe 4+ species spontaneously reduced to Fe 3+ states by the electrolyte during open-circuit storage of the charged cell.…”
Section: Single-metal-based Oxides Peculiar To Sibsmentioning
confidence: 99%
“…When Na + are extracted from the NaFeO 2 crystal lattice, vacancies are created at face‐shared tetrahedral sites with FeO 6 octahedra. Owing to that Fe 3+ are energetically stable at tetrahedral sites, Fe 3+ could easily migrate to the face‐shared sites, which is similar to LiCo x Fe 1− x O 2 . The solid‐state diffusion of Na + are thus blocked, inducing degradation of electrode properties.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 99%
“…When sodium ions are extracted from the crystal lattice, vacancies are created at tetrahedral sites that are face-shared with FeO 6 octahedra. Because trivalent iron ions are energetically stabilized at tetrahedral sites, iron ions easily migrate to the face-shared sites, similar to LiCo x Fe 1 −  x O 2 [43]. Solid-state diffusion of sodium ions is easily disturbed by iron at tetrahedral sites, leading to the degradation of electrode properties.…”
Section: Layered Oxides As Na Insertion Host Materialsmentioning
confidence: 99%
“…By contrast, and with only rare exceptions in the last 20 years, 'routine' hard x-ray XAFS [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and high-resolution XES [65][66][67][68][69][70] can only be performed at the synchrotron light sources.…”
Section: Introductionmentioning
confidence: 99%